The association between self-efficacy and completion of first-line treatment among newly referred patients with lung cancer. Issue 3 (22nd July 2022) - Kjaer, Trille K.; Hansen, Nina H. G.; Levinsen, Anne Katrine G.; Carlsen, Signe; Mellemgaard, Anders; Oksen, Marianne S.; Andersen, Ingelise; Dalton, Susanne O.
Abstract: Background: Clinical factors have an impact on the planning and completion of lung cancer treatment, but it is not well documented how psychological factors such as self-efficacy, that is, a person's belief in his or her own ability to respond to and control challenges in life, might affect completion of lung cancer treatment. We explored the association between general self-efficacy and completion of planned first-line treatment among newly referred patients with lung cancer. Methods: A total of 137 patients with lung cancer newly referred to the Oncology Department at Herlev University Hospital, Denmark, participated in this study. Data were prospectively collected through questionnaires and medical records. The Generalized Self-Efficacy Scale was used to assess self-efficacy at the time of diagnosis. Logistic regression models were used to analyze the association between self-efficacy and completion of planned first-line treatment with adjustment for age, sex, education, marital status, disease stage, and comorbidity. Results: Patients with high self-efficacy had significantly higher odds for completing first-line treatment (odds ratio 1.10; 95% confidence interval: 1.03–1.19) after adjustments. Conclusions: Patients who reported having higher self-efficacy were more likely to complete first-line treatment than patients with lower self-efficacy. This finding suggests that taking patients' psychological resources into account when planning for treatment may have potential to improve treatment for vulnerable patients with lung cancer. However, more studies are needed to confirm our findings.